Promoting non-communicable disease risks in rural area: a Community and Family Health Care - inter professional education (CFHC-IPE) activity - Diannisa Ikarumi Enisar Sangun; Dea Aryas Nugrahani; Khansa Anindya; Niken Kuntolowati (Journal of Community Empowerment for Health, 2019)
Health is an aspect that could be viewed from various age groups and factors. Risk factors found during Community and Family Health Care-Inter Professional Education visits in Pondok 2, Widodomartani, Ngemplak are the habits of people who still lacking in controlling excessive consumption of sugar, salt, and oily foods. These may lead to  many problems such as hypertension, diabetes mellitus and hypercholesterolemia. Based on the problem, our group held the community service activities focusing on health screening, particularly on the measurement of blood pressure, random blood glucose, and total cholesterol level.  This activity aims  to screen the community health condition and to raise health awareness and understanding. Therefore, people may start to take action improving their lifestyle in order to maintain their long term health status. This research is a retrospective study using secondary data obtained from health examination records at the time of community service. The health check-up was conducted on May 4, 2019. We utilize mannual mercury sphygmomanometer for blood pressure measurement and automatic skin prick test device for random blood glucose and total cholesterol level. During the health examination, we also counsel the subjects about healthy lifestyle. Sixteen people from the targeted community attended the activity. Half of the people had normal blood pressure;  1 person pre-hypertension; 4 persons stage I hypertension, and 3 persons stage II hypertension.  For random blood glucose measurement, only 1 resulted in high random blood glucose whilst others were within normal limit.  Total cholesterol level was examined to 9 people with history of hypercholesterolemia with the following results; 2 people had high level, 2 people had borderline-high level ,and the rest had normal level. Most of the people within the community had good health status. This kind of activity can be routinely conducted not only to screen community health status but also to promote health awareness.